Bolstering IoT security. Issue 5 (May 2021) - Unknown
Abstract : The UK Government is pushing ahead with legislation to make Internet of Things (IoT) devices more secure. Meanwhile, Microsoft has warned of more than 25 flaws it has discovered in such devices.